2005
DOI: 10.1111/j.1478-3231.2005.01086.x
|View full text |Cite|
|
Sign up to set email alerts
|

Instant diagnosis of spontaneous bacterial peritonitis using leukocyte esterase reagent strips: Nephur‐Test® vs. MultistixSG®

Abstract: Leukocyte esterase reagent strips may provide a rapid bedside diagnosis of SBP and thereby shorten time to appropriate management. The Nephur-Test appeared to out-perform MultistixSG. These tests might be particularly useful in ambulatory settings or whenever ascites fluid analysis is not rapidly available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 16 publications
3
52
1
Order By: Relevance
“…The sensitivity and specificity of the reagent strip (Aution sticks®; A. Menarini Diagnostics, Firenze, Italy) were 96% and 89%, respectively [26]. Other studies have been carried out in order to confirm the performance of different reagent strips in SBP diagnosis in inpatient and outpatient settings reaching similar results [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The sensitivity and specificity of the reagent strip (Aution sticks®; A. Menarini Diagnostics, Firenze, Italy) were 96% and 89%, respectively [26]. Other studies have been carried out in order to confirm the performance of different reagent strips in SBP diagnosis in inpatient and outpatient settings reaching similar results [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 69%
“…Recently, Sapey et al showed that different brands can achieve different accuracy in the diagnosis of SBP [33]. The authors compare two different reagent strips (Multistix SG x Nephur-Test) finding that the Nephur-Test seems to out-perform Multistix SG.…”
Section: Discussionmentioning
confidence: 99%
“…The first study [36] , published in 2002, involved 72 cirrhotic patients, nine of whom had SBP, reported a sensitivity and a specificity of 100% for the urinary strips in the diagnosis of SBP. After this successful result, in the following years a number of reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] evaluated the urine strip test for the diagnosis of SBP (Table 2). These studies reported promising and encouraging results, with the sensitivity of urinary strips for the diagnosis of SBP ranging between 85% and 100% and the specificity between 90 and 100%.…”
Section: The Determination Of Pmn Cells In the Ascitic Fluidmentioning
confidence: 99%
“…Compared with the manual PMN count ('gold standard'), LERS were found to have sensitivity ranging from 45 to 100%, specificity ranging from 81 to 100%, PPV value ranging from 42 to 100% and NPV ranging from 87 to 100%. [4][5][6][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Similarly, the published studies in which Multistix reagent strips were used have also shown widely variable test results (Table 3). 4,[12][13][14][17][18][19][20]24 In an only study from India, authors have shown the Multistix strip's sensitivity, specificity, PPV and NPV of 97%, 89%, 87% and 83% respectively using a cut-off of grade 2.…”
Section: Uriscanmentioning
confidence: 99%